Hellandite-(Y)–hingganite-(Y)–fluorapatite retrograde coronae: a novel type of fluid-induced dissolution–reprecipitation breakdown of xenotime-(Y) in the metagranites of Fabova Hoľa, Western Carpathians, Slovakia. (24th August 2022) - Ondrejka, Martin; Molnárová, Alexandra; Putiš, Marián; Bačík, Peter; Uher, Pavel; Voleková, Bronislava; Milovská, Stanislava; Mikuš, Tomáš; Pukančík, Libor
Abstract: Two contrasting reaction coronae were developed around rare earth element (REE) accessory phosphates in Variscan metagranitic rocks, which have been overprinted by Alpine blastomylonitisation from the Fabova Hol'a Massif, in the Veporic Unit, Western Carpathians, Central Slovakia. The Th–U–Pb total EPMA age determination of primary magmatic monazite-(Ce) from the metagranite indicates a Carboniferous (Mississippian, Tournaisian) age of 355 ± 1.9 Ma. Monazite-(Ce) breakdown resulted in impressive, though common, fluorapatite ± Th-silicate + allanite-(Ce) + clinozoisite coronae. The alteration of xenotime-(Y) produced a novel type of secondary coronal micro-texture consisting of a massive fluorapatite mantle zone and tiny satellite crystals of hellandite-(Y) [(Ca, REE)4 Y2 Al□2 (B4 Si4 O22 )(OH)2 ] and hingganite-(Y) [Y2 □Be2 Si2 O8 (OH)2 ] of ~1–5 μm, and rarely ≤10 μm in size. The localised occurrence of Y–B–Be silicates, which are associated closely with other secondary minerals, suggests the involvement of B and Be during the metasomatic alteration transformation of xenotime-(Y). General reactions for monazite-(Ce) and xenotime-(Y) decomposition, including the fluids involved, can be written as follows: Mnz + (Ca, Fe, Si, Al and F)-rich fluid → FAp + Ht + Aln + Czo; Xtm + (Ca, Fe, Si, Al, F, B and Be)-rich fluid → FAp + Hld + Hin + Czo. The granitic rocks underwent Early Cretaceous burial metamorphism under greenschist- to lower amphibolite-facies P – T conditions. Subsequently, Alpine post-collisional uplift and exhumation of the Veporic Unit, starting from the Late Cretaceous epoch, was accompanied by a retrograde tectono-metamorphic overprint; the activity of external fluids, caused the formation of secondary coronae minerals around monazite-(Ce) and xenotime-(Y). A portion of B (± Be) should have been liberated from the metagranite feldspars, micas, or xenotime-(Y) enriched in (Nb, Ta)BO4 (schiavinatoite or béhierite) components. However, the principal source of B and Be in fluids necessary for the production of hellandite and hingganite, was probably of external origin from adjacent magmatic, metamorphic, or sedimentary rocks (Permian granites, rhyolites and sedimentary rocks, and Palaeozoic metapelites).